AKSESIBILITAS PETANI KECIL PADA SUMBER KREDIT PERTANIAN DI TINGKAT DESA: STUDI KASUS PETANI PADI DI NUSA TENGGARA BARAT - ADE SUPRIATNA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2008)
One problem in rice production at village level is a lack of capital and credit has become a partof farm economy. This study was conducted in 2003 and took place in Nusa Tenggara Barat (NTB).The objectives of study were:(i) to identify the existing sources of agricultural credit at the villagelevel, (ii) to identify the sources of credit to which small farmers have been access to meet theirfinancial needs, and (iii) to identify the ideal scheme of credit that suitable for small farmers. Theresults shown that the oldest sources of loan at the village level were the informal institutions such asdaily Bank, money lender, rice trader, input trader, and rice miller. The formal institutions wereestablished later namely KUD in 1977, BPR in 1988, BRI Unit Desa in 1996, and Pawnshop in 2001.Small farmers and landless farmers were generally access to the informal institutions. The scheme ofinformal institutions provided a loan at high interest rate, but the other ones were very suitable forsmall farmers, such as no collateral, simple procedure, and fast to obtain. Otherwise small farmerscould not access to the formal institutions that served a loan at low interest rate, because of: (a) theydid not have any collateral required by the scheme, especially land certificate, (b) monthly repaymentof credit was not suitable for rice farm that have a seasonal cycle of production, and (c) they wereunfamiliar with complex procedure of credit. A lot of small farmer hopes a credit with collateral ofmoving goods (no land sertificate), interest rate from 18 to 24 percent per year, credit in cash, andshort term credit.